The Japanese version of the Richards‐Campbell Sleep Questionnaire: Reliability and validity assessment. Issue 3 (28th March 2019) - Murata, Hiroaki; Oono, Yoko; Sanui, Masamitsu; Saito, Keita; Yamaguchi, Yoko; Takinami, Masanori; Richards, Kathy C.; Henker, Richard
Abstract: Aims: The purpose of this study was to determine the reliability and validity of the Japanese version of the Richards‐Campbell Sleep Questionnaire as a measure of sleep among intensive care unit patients in a Japanese hospital. Design: Cross‐sectional survey. Methods: The Richards‐Campbell Sleep Questionnaire was initially translated into Japanese using the back‐translation method. Validity was evaluated by determining the association between sleep efficiency, measured using simplified polysomnography, and the total score on the Japanese version of the Richards‐Campbell Sleep Questionnaire. Adult non‐intubated intensive care unit patients who completed the five‐item visual analogue scale underwent polysomnography for one night. Reliability was tested using Cronbach's alpha coefficient. Results: Thirty‐three patients were included in the analysis. After excluding four patients with subsyndromal delirium, the Pearson correlation coefficient was 0.602 ( p = 0.001). Cronbach's alpha coefficient was 0.911. Conclusion: The Japanese version of the Richards‐Campbell Sleep Questionnaire could be used as an alternative to polysomnography when assessing sleep quality in lucid intensive care unit patients.